Cultural references translation norms in the queue from Arabic to English - Alharahsheh, Abdelrauof Meqbel AH; Moindjie, Mohamed Abdou; Debbita Tan, Ai Lin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Translating literary works is a challenging task, especially when attempting to integrate numerous linguistically, artistically, and culturally varied languages. The main objective of this research is to describe the initial norms that regulate the translation of Arabic cultural references translated in Basma Abdelaziz's Arabic novel, The Queue. This novel by Basma Abdelaziz was chosen for examination because it contains a lot of cultural references that reflect cultural values. To detect translation shifts and techniques used by the Queue’s translator, the major principles and components of Toury's theory of norms, Newmark’s classification of cultural items, and translation techniques proposed by Vinay and Darbelnet (1995) will be used. The techniques for translating Arabic cultural references reflect the translators' individual attitudes toward ST norms as well as their adherence to linguistic and cultural standards prevalent in the TL setting. Overall, there is some heterogeneity in the degree of leaning toward SL or TL norms. According to Toury's norms model, the general trend of translational norms appears to lean more towards the acceptability pole than the adequacy pole, implying that a TL-oriented strategy is preferred. The study reveals that when translating cultural references into English, the Queue's translator used four primary strategies: modulation, transposition, adaption, and deletion. These translation strategies utilized by the Queue’s translator may provide the target reader with altered meaning of the cultural references will have an impact on the portrayal of the Queue and provide the target readers with a significantly altered version of the text These translation strategies utilized by the Queue’s translator may provide the target reader with altered meaning of the cultural references text.